Crisis del sistema educativo costarricense a consecuencia de las huelgas y la pandemia: efectos en la alfabetización estadística - Chaves Esquivel, Edwin (2020)
This essay refers to the crisis that has affected the Costa Rican educational system as a consequence of the educators’ strikes and student stoppages in 2018 and 2019, as well as the pandemic caused by the SARS-CoV-2 virus in the year 2020. These events are generating a widening of the social gap in education, which can have dramatic consequences for the social wellness of the country. Within the framework of the implementation of the Reform of Mathematics Education, the decision of the Ministry of Public Education (MEP) of Costa Rica to eliminate, almost completely, the area of Statistics and Probability in the prioritization of content and skills within the curricular changes for this 2020 as a result of the pandemic is analyzed. That decision ignores the potential of this area to describe and analyze the data generated daily as a result of the direct and indirect effects of the pandemic, which should be an important input in education.